Impact of crack cocaine on salivary nucleic acids, enzymes, esters, and lipids: A fourier-transform infrared spectroscopy study - Zucco, Gabriela Ribeiro [UNESP]; Cardoso de Oliveira, Taís Maria [UNESP]; Pereira da Silva, Thaís Xavier [UNESP]; Marques, Sandra Silva; Sabbag, Fernando; Ribeiro de Araújo, Marcelo; Zerbinati, Rodrigo Melim; Braz-Silva, Paulo Henrique; Lindoso, José Ângelo; Jimenez Teodoro Nepomuceno, Gabrielle Luana; Foiani, Letícia; da Silva Martinho, Herculano; et al. (Elsevier, 2025)
Objective: This study aims to analyze saliva composition in crack users using vibrational spectroscopy. Material and Methods: A total of 90 participants were meticulously selected and divided into three groups, each comprising 30 individuals. All participants met the criterion of having no observable clinical changes in the oral mucosa. The groups included active crack users with a minimum usage duration of 30 days, ex-crack users, and non-crack users. Rigorous inclusion and exclusion criteria were applied during participant selection to ensure the study's precision. Saliva analysis was performed using vibrational spectroscopy with FTIR (Fourier-transform Infrared spectroscopy). Results: Pre-processed spectra enabled statistical comparability. Salivary biomarkers revealed clinical implications, including findings related to xerostomia, caries, and periodontal or systemic conditions such as lung cancer. Conclusion: The research uncovers significant compositional differences in the saliva of current users, former users, and non-users of crack. This nuanced understanding contributes to the discourse on substance abuse, highlighting the potential of saliva analysis for discerning different stages of crack use. The investigation suggests options for further exploration in clinical and forensic contexts, promising advancements in addiction research and diagnostics.
Keywords: Addiction; Cocaine; Crack cocaine; FTIR; Liquid biopsy; Saliva; Spectroscopy